2006
DOI: 10.4319/lom.2006.4.38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different sampling designs and methods on the estimation of secondary production: A simulation

Abstract: IntroductionIn marine studies, the secondary production of macrobenthic populations can be estimated in a number of ways. Classic techniques can be broadly classified as cohort-and size-based. Prominent in the first group are the Allen-curve, incrementand removal-summation, and instantaneous-growth methods. The second group consists mainly of the size-frequency, massspecific growth rate, and mass-specific mortality rate methods.These estimation techniques, and numerous variants thereof, have been described, e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…On the other hand, simulation studies using "asynchronous" cohorts, i.e. not born all on the same day (as is true of the species examined here), have shown the sizefrequency method to be biased low [55,58].…”
Section: Methods Summarymentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, simulation studies using "asynchronous" cohorts, i.e. not born all on the same day (as is true of the species examined here), have shown the sizefrequency method to be biased low [55,58].…”
Section: Methods Summarymentioning
confidence: 72%
“…The first of these is the well-known increment summation method, which sums the growth increments in biomass during a cohort's lifespan. The version we used was developed by Cusson et al [55] and is described as their method "IS-3." The second is the size-frequency method [56], which sums the loss of biomass between successive size classes and weights them by the number of days between surveys.…”
Section: Methods Summarymentioning
confidence: 99%
“…This method of assessing annual production by summing seasonal production estimates is superior to calculations using only once-per-year estimates of numbers and individual weights (as explained by Dekker & Beukema 2007). Sampling more frequently than twice annually would certainly have resulted in more precise estimates of annual P, as shown in a simulation study by Cusson et al (2006). They show ed that both bias as well as random errors declined with sampling frequency.…”
Section: Estimation Of Productionmentioning
confidence: 97%
“…As a consequence of some assumptions (e.g. on the course of the decline of numbers of cohort members between samplings), the precision of direct estimates is not perfect, but will be satisfactory in most cases (Cusson et al 2006). Direct methods are relatively simple and straightforward if separate cohorts can be distinguished.…”
Section: Secondary Productionmentioning
confidence: 99%
“…Several studies investigated effects of sampling design on estimation of secondary production (Cushman et al ; Morin et al ; Cusson et al ). They showed that the choice of sampling period and frequency affect the estimation, and inappropriate choices can lead to high bias in production estimates.…”
mentioning
confidence: 99%